(untitled) (Baghdad Science Journal, 2013)
This study is aimed to use the aerobic packed bed in biotreatment of the wastewater which is discharge from AL-KARAMA teaching hospital in Baghdad. The performance of packed-bed treatment method was examined for elimination of the organic compounds from wastewater under aerobic conditions. In this research different parameters were studied. They were: inoculums concentration, circulation rate of wastewater through the bed, packing type and the temperature. Results showed that the system efficiently removed about 82% of the chemical oxygen demand (COD) and 80% of the Biological oxygen demand (BOD). Percent reduction in turbidity was about 92% and reduction in nitrate concentration was about 87%. It was found that best performance of the packed bed method was obtained at temperature of 37 oC, circulation rate of 10 L/min and inoculums concentration of 3%.